Description of a new species of Chimarrhometra Bianchi, 1896 (Hemiptera: Heteroptera: Gerridae) from China - Ye, Zhen; Zhou, Yanyan; Bu, Wenjun (Zootaxa, 2016)
The genus Chimarrhometra Bianchi is recorded for the first time from China and C. yunnanensis sp. n. is described. Photographs of the male and female dorsal habitus and male and female genitalic structures are provided. Habitat photos and a distribution map for the species of Chimarrhometra also are provided.